Pelaksanaan Program Pembiasaan Keagamaan Dalam Pembentukan Karakter Religius Peserta Didik - Minahul Mubin; Moh. Arif Furqon (Jurnal Riset Madrasah Ibtidaiyah, 2023)
Religious character education is one of the characters that need to be developed in students in cultivating behavior in accordance with Islamic religious teachings which are based on the Qur'an and Hadith. There are many students who act not in accordance with Islamic religious values ​​that apply both at school and in society. So religious character education needs to be implemented and realized. One important factor in growing the religious character of students is religious habituation. This study aims to determine the extent to which the effects of religious habituation in the formation of religious character at MI Maliaul Hikam. This research is qualitative research in which the data collected is not in the form of numbers but data comes from interview scripts, field notes, personal documents, memo notes, and other official documents carried out at MI Malihatul Hikam validly and can be accounted for. Activities before to after learning are an effective way of habituation to being able to foster the religious character of students, religious habituation activities can be trained and accustomed to every day. The results of religious habituation which are carried out every day and are repeated will always be embedded and can be remembered by students so that it is easy to do them without having to be warned again by the teacher.